The DuPont System Re-examined: Operating Efficiency, Asset Productivity, and Earnings Growth in Indonesia's Capital-Intensive Public Utility Sector - Listri Herlina (CV. Era Digital Nusantara, 2026)
Earnings growth is a crucial indicator for assessing corporate financial performance, especially for state-owned public utilities like PT PLN (Persero), which face dual compression from operating costs and capital efficiency. This study aims to examine the effect of Operating Profit Margin (OPM) and Total Asset Turnover (TATO) on Earnings Growth at PT PLN (Persero). Employing a causal-associative quantitative approach, the data comprises 30 quarterly time-series observations (Q3 2017–Q4 2024), analyzed using multiple linear regression. The partial test results reveal statistical insignificance for both OPM and TATO. However, rather than treating the extreme Variance Inflation Factor (VIF = 521.62) as a mere econometric defect, this study theoretically reframes it as empirical proof of deep structural integration between cost efficiency and asset productivity in capital-intensive industries. Consequently, the simultaneous test (F-test) proves that OPM and TATO collectively exert a highly significant effect on Earnings Growth (F = 37.01; p = 0.000), explaining 73.3% of the variance. Theoretically, this statistical contradiction confirms the DuPont System's multiplicative nature, explaining the periodic earnings contraction anomaly in odd quarters where dual compression occurs. Practically, the study implies that management cannot rely on atomistic operational efficiency; instead, they must synchronize minimum fixed asset capacity utilization with operational hedging to mitigate profit volatility under strict state tariff regulations.